Mobility concepts and the impact of changing circumstances: a strategic approach to innovation and market dynamics regarding mobility as a service. - Rapp, Tobias (My University, 2019)
Population growth, urbanization and climate change are regarded as the megatrends of today's society. This goes hand in hand with a high consumption of resources and pollution. Indeed, these megatrends are mutually reinforcing. A significant part of this is due to mobility in daily life. Technological change such as digitalization creates innovative concepts to improve mobility and to deal with these changing circumstances. A comprehensive concept in this respect is mobility as a service. This thesis focuses on the identification of the mobility ecosystem and thus on the various stakeholders. First of all, it deals with the definition of mobility as a service in order to identify the ecosystem in particular in the second step. Mobility is classified and analyzed by working on the basis of secondary literature and a quantitative as well as qualitative methodology in expert interviews. This allows conclusions about the relationships, prerequisites and obstacles within the ecosystem and stakeholders. The results of the thesis suggest that collaboration within the ecosystem is a prerequisite for the implementation of mobility as a service. Furthermore, that mobility as a service should ensure adaptability, since local infrastructures differ between Germany, USA and China, but also within these countries. This adaption process is iterative. The obstacles are interoperability and the willingness to cooperate. Moreover, the results imply that mobility as a service will assert itself more quickly in urban areas due to factors such as the pressure to act and the availability of mobility services as well as the number of customers.
Keywords: Mobilität; Nahverkehrskonzept; Verkehr; Verkehrskonzept; Digitalisierung; Verkehrsinfrastruktur; Dienstleistung; Mobilitätskonzept; Verkehrsplanung; Folgewirkung; Ökosystem; Umweltverschmutzung; Nachhaltige Mobilität; Vergleichsuntersuchung